Optimal Growth and Biomass of Centella asiatica Using a Twin-Bottle Temporary Immersion Bioreactor - Thanakorn Wongsa; Anupan Kongbangkerd; Boworn Kunakhonnuruk (Horticulturae, 2023)
Centella asiatica or gotu kola has long been used as a traditional medicinal plant. Here, immersion times and culture systems on growth and biomass production of C. asiatica were investigated using a twin-bottle, temporary immersion system. Results indicated that all immersion times gave 100% survival, with a 5 min immersion 12 times/day, providing the highest number of new shoots (3.6 shoots/explant), leaves (10.2 leaves/explant), roots (8.3 roots/explant), and fresh and dry weights of clumps (5.06 g fresh weight and 0.48 g dry weight/clump). The temporary immersion system resulted in more than a three-fold increase in biomass accumulation, with the highest average number of new shoots, leaves, and roots compared to a semi-solid system.